Characterisation of putative virulence factors in adherent-invasive Escherichia coli - Cogger-Ward, Robert (2020)
Crohn’s disease (CD) is a chronic inflammatory bowel disease. CD is driven by a synergy of predisposing genetic variants, diet, gut colonisation with a perturbed pro-inflammatory microbiome, and infection with CD-associated pathobionts, including Adherent-Invasive Escherichia coli (AIEC). AIEC is a non-diarrhoeagenic intestinal E. coli pathotype, the virulence of which is characterised by adhesion to and invasion of intestinal epithelial cells (IECs); intracellular replication within IECs and macrophages; flagella-mediated motility; and biofilm formation.